Enhancing quality education with 5Ds design thinking-innovative pedagogy for creative planning in cultural projects - Zhang, Shiyong; Vate-U-Lan, Poonsri; Sivapirunthep, Panneepa (International Journal of Evaluation and Research in Education (IJERE), 2025)
This quantitative study addressed the declining interest of young people in traditional culture and the lack of empirical evidence on innovative pedagogies to enhance student engagement and academic achievement. The research examined the efficacy of a novel 5Ds design thinking-based pedagogy—discover, define, design, develop, and deploy—in enhancing students’ design thinking mindsets and academic performance in cultural project planning. The study was conducted at Shanxi University of Finance and Economics and compared the average scores of an experimental group with 42 students (EG, n=42) and a control group (CG, n=37) from five classrooms with 194 students. The EG actively engaged with the 5Ds pedagogy, progressing through each stage to collaboratively develop cultural projects, while the CG received traditional instruction. Utilizing a 30-item design thinking mindset measurement (DTMM) scale and an 88-question achievement test, the study revealed significant improvements in the EG’s human-centeredness and mindfulness. Post-intervention academic achievement scores were substantially higher in the EG (M=60.09) compared to the CG (M=47.54), with a significant difference (t=-12.114, p<0.001). These findings demonstrated the effectiveness of the 5Ds pedagogy in enhancing critical thinking, adaptability, and creativity, providing compelling evidence for integrating design thinking methodologies into higher education curricula to reinvigorate cultural education and improve student engagement.